431PAn in vitro evaluation of CYP2D6 enzymatic inhibition activities of a Chinese herbal medicine formulation (Xiang Bei Yangrong Tang) for the management of cancer-related fatigue. (24th November 2019) - Yap, N Y; Ho, H K; Zheng, H F; Tan, C J; Toh, Y L; Ng, C C; Chan, A
Abstract: Background: Breast cancer survivors (BCS) often experience cancer-related fatigue (CRF), a distressing condition which does not have an effective standardised pharmacological intervention. Xiang Bei Yangrong Tang (XBYRT), a modified herbal traditional Chinese medicine (TCM) decoction, is formulated for the management of CRF in BCS. In this in vitro study, we evaluated the herb-enzyme inhibition for 9 of the herbal TCMs from the XBYRT formulation, on CYP2D6 activity. Methods: The XBYRT herbal components evaluated were Radix Astragaliseu Hedysari, Radix Codonopsis Pilosulae, Rhizoma Atractylodis Macrocephalae, Poria cocos, Radix Paeoniae Alba, Fructus Ligustri Lucidi, Rhizoma Cyperi, Radix Polygalae and Bulbus Fritillariae Thunbergii. Varying concentrations of the herbal TCMs were assayed for herb-enzyme inhibition using the Vivid P450 CYP2D6 assay kit. The percentage inhibition for the maximum XBYRT concentration and the half maximal inhibitory concentrations (IC50 ) were determined. The maximum XBYRT concentration was calculated based on the total dosage of herbal components consumed, without accounting for first pass metabolism. The IC50 was calculated using the non-linear regression from GraphPad Prism 5. Results: Assayed at the maximum XBYRT concentration, herbal components exhibiting the highest inhibition levels were Radix Codonopsis Pilosulae (56.8%), Poris cocos (45.0%), Fructus Ligustri Lucidi (42.9%) and Radix Paeoniae Alba (35.5%). The IC50 values of these four herbal components were 481µg/ml, 572 µg/ml, 447 µg/ml and 475 µg/ml respectively. The other 5 herbal components exhibited <30% inhibition at the maximum XBYRT concentrations. Conclusions: Components of XBYRT display potential CYP2D6 enzymatic inhibition activities. Hence, caution should be taken with the concomitant usage of XBYRT with drugs that are CYP2D6 substrates such as tamoxifen. In vivo and clinical studies are required to ascertain the actual effects of these herbal components on drug metabolism. Legal entity responsible for the study: The authors. Funding: Ministry of Health Singapore. Disclosure: All authors have declared no conflicts of interest.